Parental Socioeconomic Status and Grade VIII Learning Outcomes: Evidence from SMP Negeri 1 Telaga (Gorontalo, Indonesia) - Serly Monalisa Abudi; Roy Hasiru; Rierind Koniyo; Meyko Panigoro; Abdulrahim Maruwae (Yayasan Pendidikan Sudirman Mandiri, 2026)
This study investigates the effect of parental socioeconomic status on the learning outcomes of Grade VIII students at SMP Negeri 1 Telaga, Indonesia. Recognizing the increasing concern over educational inequality, the research aims to examine how family background influences students’ academic achievement within a localized school setting. A quantitative, causal-comparative method was employed, involving 68 students selected through proportional random sampling from a population of 271. Data were collected using structured questionnaires validated through Pearson Product-Moment correlation and tested for reliability using Cronbach’s Alpha. The results reveal that parental socioeconomic status significantly affects student learning outcomes across cognitive, affective, and psychomotor domains. The regression model (Ŷ = 18.234 + 0.739X) indicates a positive relationship, with a t-value of 10.221 and a significance level of 0.000. The coefficient of determination (R² = 0.613) confirms that 61.3% of the variance in learning outcomes is explained by socioeconomic status, with parental income and education emerging as dominant factors. The affective domain exhibited the highest mean score, followed by cognitive and psychomotor domains, highlighting the importance of emotional and motivational support at home. These findings align with prior research emphasizing the impact of SES on educational performance. The study suggests the need for tailored interventions addressing SES-related barriers to enhance equity in academic outcomes. The research contributes localized evidence to the broader discourse on education and social determinants, providing a model for policy and school-level responses in similar socio-educational contexts.